Precautionary Saving with Changing Income Ambiguity - KAJII, Atsushi (Institutional Knowledge at Singapore Management University, 2016)
We study a two-period saving model where theagent’s future income might be ambiguous. Our agent has a version of the smoothambiguity decision criterion (Klibano, Marinacci and Mukerji (2005)), where theagent’s perception about ambiguity is described by a second-order belief overfirst-order risks. We model increasing ambiguity as a spreading-out of thesecond-order belief. We show that under a “Risk Comonotonicity” condition, ouragent saves more when ambiguity in future income increases. We argue that thecondition is indispensable for our result.